PRICE BEHAVIOR ANALYSIS OF BRAZILIAN YERBA MATE EXPORTED TO URUGUAY BETWEEN 1997 AND 2018 - Heimann, Jaqueline de Paula; Machado, Marco Antonio Dias; Hoeflich, Vitor Afonso; Leodoro da Silva, João Carlos Garzel; de Paula, Thiago Rodrigues; Costa Junior, Francisco (Floresta, 2021)
The objective of this study was to evaluate price seasonality of the Brazilian Yerba mate exported to the Uruguayan market, serving as a basis for decision-making to the producers. For this purpose, we collected data on Brazilian yerba mate exports to Uruguay, available in the ALICE-WEB System, which, after deflation, were used to determine the Seasonal Index for different periods between 1997 and 2018 The results showed that the market for yerba mate does not present regular historical cycles, the prices of the Brazilian product in the Uruguayan market suffer constant falls and increases. Nevertheless, it is possible to observe a long-term trend of increasing the real price of the product at an average rate of 0.33% per month. It is possible to conclude that the price of Brazilian yerba mate in the Uruguayan market was in the ascendancy until the beginning of 2015, when the Uruguayan Justice instituted an investigation to investigate the presence of cadmium and lead at levels above the allowed ones in the Brazilian product. At the end of the study period, there was a slight tendency to recover prices, however, only new studies will be able to verify if the price of Brazilian yerba on the Uruguayan market will reach levels similar to those registered before the judicial embargo. Keywords: international trade; seasonality; competitiveness.